IMPLEMENTASI PERATURAN PRESIDEN REPUBLIK INDONESIA NOMOR 86 TAHUN 2018 TENTANG REFORMA AGRARIA DI KABUPATEN INDRAGIRI HULU TAHUN 2020-2021 - Fahkrur Rifqi; Geovani Meiwanda (Universitas Halu Oleo, 2022)
In order to improve justice in land tenure and ownership as well as improve people's welfare, the President of the Republic of Indonesia make policies on Agrarian Reform as stated in Presidential Regulation Number 86 of 2018 where the efforts made are to implement Land Redistribution. This research is intended to see the implementation of Land Redistribution carried out in Indragiri Hulu District in 2020 and 2021, which at the end of its implementation experienced a decrease in targets and still found fragmentation in the bureaucratic process. This research uses qualitative research method thas uses data collection techniques, namely interviews and documentation. The results shown in this research are that the implementation of Land Redistribution carried out in Indragiri Hulu District in 2020 and 2021 has gone quite well, but in its implementation there are still few problems that cause delays in the completion of the program.